Protein kinase D displays intrinsic Tyr autophosphorylation activity: insights into mechanism and regulation. Issue 14 (23rd July 2018) - Cobbaut, Mathias; Derua, Rita; Parker, Peter J.; Waelkens, Etienne; Janssens, Veerle; Van Lint, Johan
Abstract : The protein kinase D (PKD) family is regulated through multi‐site phosphorylation, including autophosphorylation. For example, PKD displays in vivo autophosphorylation on Ser‐742 (and Ser‐738 in vitro ) in the activation loop and Ser‐910 in the C‐tail (hPKD1 numbering). In this paper, we describe the surprising observation that PKD also displays in vitro autocatalytic activity towards a Tyr residue in the P + 1 loop of the activation segment. We define the molecular determinants for this unusual activity and identify a Cys residue (C705 in PKD1) in the catalytic loop as of utmost importance. In cells, PKD Tyr autophosphorylation is suppressed through the association of an inhibitory factor. Our findings provide important novel insights into PKD (auto)regulation. Abstract :